Analisis Swot Dalam Strategi Pengembangan Pemasaran Agen Kemitraan XYZ Express (Studi Kasus Di Kecamatan Rajeg, Kabupaten Tangerang) - Fitriyanto, Abdul Rouf; Soerahman, Soerahman; Sucipto, Eko Hadi Sucipto; Aqshal, Mochamad (Journal Industrial Manufacturing, 2025)
This study aims to analyze the application of the SWOT method in formulating marketing strategies for XYZ Express in the Rajeg area, Tangerang Regency, focusing on identifying internal and external factors affecting the company's performance. With the research findings, the Internal Factor Analysis Summary (IFAS) score was 0.78, indicating the dominance of strengths over weaknesses, while the External Factor Analysis Summary (EFAS) score was –0.50, suggesting that the external environment is largely influenced by threats. The combination of these values places the company in quadrant II or ST strategy, where internal strengths are leveraged to address external challenges. The company's main strengths include fast and accurate delivery, competitive pricing, and real-time tracking services, while weaknesses are observed in limited promotion, payment method variety, and packaging security. External threats consist of intense competition, rising fuel costs, dependence on technology, and strict government regulations. Based on these conditions, recommended strategies include strengthening core services to maintain competitive advantages, diversifying services by adding payment options and enhancing packaging security, and expanding market reach through more effective digital marketing. Additionally, optimizing technology utilization, developing human resource competencies, and improving operational efficiency are necessary to reduce costs and adapt to external changes. With the implementation of an integrated and adaptive strategy, XYZ Express is expected to expand its market share while reinforcing competitiveness in the increasingly dynamic courier service industry.Keywords: SWOT, marketing strategy, diversification, logistics company, delivery service